PET/CT-based target volume definition in involved-site radiotherapy for treatment of early-stage nodal follicular lymphoma - Wark, Antje; Kim, Ji-Young; Mavriopoulou, Eleni; la Fougère, Christian; Wiegel, Thomas; Scholz, Christian W.; Baues, Christian; Li, Minglun; Gauler, Thomas; Combs, Stephanie; Herfarth, Klaus (Strahlentherapie und Onkologie, 2025)
Recent advancements in imaging, particularly 18F-fluorodeoxyglucose positron-emission tomography-computed tomography (FDG-PET/CT), have improved the detection of involved lymph nodes, thus influencing staging accuracy and potentially treatment outcomes. This study is a post hoc analysis of the GAZAI trial data to evaluate the impact of FDG-PET/CT versus computed tomography (CT) alone on radiation target volumes for involved-site radiotherapy (IS-RT) in early-stage follicular lymphoma (FL).